Applications of Carbon Nanotubes in CFx Electrodes for High-power Li/CFx Batteries. Issue 6 (2016) - Zhang, Qing; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.
ABSTRACT: Carbon monofluoride (CFx ) has been extensively used as a reliable cathode material in lithium primary batteries because of its high energy density and long shelf life. However, the implementation of Li/ CFx batteries in high-power applications is limited by the low power capability resulting from the insulative nature of CFx material. In this work, we incorporated multi-walled carbon nanotubes into CFx electrodes and studied the impact on the electrochemical performances when CNTs were used as a conductive additive material and current collector substrate. Our work demonstrated the promising utilization of CNTs in CFx electrodes in improving the practical capacity and power capability of Li/ CFx batteries.